22.0k views
0 votes
Find the difference. (4x 2 - 6x + 8) - (3x 2 - 6x + 2)

x^2 + 6
7x^2 - 12x - 6
x^2 + 12x + 6
x^2 - 12x - 6

User Zoliqa
by
5.2k points

2 Answers

3 votes

Answer:

A. x^2 + 6

Explanation:

(4x^2 - 6x + 8) - (3x^2 - 6x + 2) =

The first set of parentheses is unnecessary, so just remove it.

= 4x^2 - 6x + 8 - (3x^2 - 6x + 2)

To remove the second set of parentheses, change the sign of each term inside.

= 4x^2 - 6x + 8 - 3x^2 + 6x - 2

Now combine like terms.

= x^2 + 6

User Nattyddubbs
by
4.9k points
5 votes

For this case we must find the difference of the following polynomials:


(4x ^ 2-6x + 8) - (3x ^ 2-6x + 2) =

Taking into account that:


- * - = +\\+ * - = -

We have:


4x ^ 2-6x + 8-3x ^ 2 + 6x-2 =\\x ^ 2 + 0x + 6 =\\x ^ 2 + 6

Answer:


x ^ 2 + 6

User Gnerkus
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.